Donation of organs and tissues for transplantation: Theoretical contributions. - de Araujo Nogueira, Maicon; de Mendonça Flexa, Joana Kátia; Reis Montelo, Itamar; de Souza Lima, Lorena; Oliveira Maciel, Danielle; Moita Sá, Antônia Margareth (Brazilian Journal of Implantology and Health Sciences, 2020)
This bibliographic review study aimed to make theoretical considerations related to the process of organ and tissue donation for transplantation in Brazil. The information source was composed of relevant publications from the Brazilian Association of Organ Transplants, as well as articles found in Latin and American databases, in addition to the current legislation. The increase in the donation rate depends on a broad and systematic look at the technical and legal issues inherent to the donation process. To strengthen this process, it is recommended to incorporate the social approach and the ethical perspective, based on technical and legal understanding and respect for the right of autonomy of potential donors and their families. Actions that ensure ethical-legal management presuppose a commitment to the quality and safety of the donation process, which must be strictly pursued by professionals in this context.